THE ROLE OF DIGNITY THERAPY IN ELDERLY PATIENTS: A COMPREHENSIVE SYSTEMATIC REVIEW - Mengyao Zhuansun; Lamei Liu; Tong-yao Xu; Yu-meng Qian; Meng-jie Sun; Jia-nan Wang; Ronnell Dela Rosa; Peng Wang (Indonesian Journal of Community Health Nursing, 2023)
Introduction: Dignity therapy is a brief psychotherapy that can reduce dignity-related distress and improve the quality of life for cancer patients. However, the experience of older patients is comparable to that of those with advanced cancer, little emphasis has been devoted. Aim: To evaluate and summarize the effectiveness of dignity therapy in managing elderly non-cancerous patients   Method: A mixed methods systematic review was conducted and assess their quality using the Joanna Briggs Institute's evaluation tools. 8 databases of literature including Cochrane Library, PubMed, SCOPUS, Web of Science, EMBASE, CINAHL(EBSCO), PsycINFO(OVID), and CBM were searched with search terms of “Dignity therapy” and “elderly”.   Results: 12 studies—3 RCTs, 5 qualitative studies, 2 mixed-methods studies, and 2 cross-sectional studies—out of 1615 studies were screened. Quantitative and qualitative results were separated into groups with quantitative groups containing the dignity-related distress, depression, and quality of life, and qualitative groups including remembrance of the past, meaning of life, pain of illness, and wishes for family members. Conclusion: Evidence suggests that dignity therapy is beneficial and can be applied to non-cancer patients. The patient's baseline level of distress may affect outcomes, making it more difficult to intervene with patients if they are too distressed, but the effect may be less pronounced if the patient's distress level is low.